2022
DOI: 10.12688/f1000research.124586.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival status and predictors of mortality among mechanically ventilated COVID-19 patients in Addis Ababa COVID-19 Care Centers, Ethiopia: A survival analysis

Abstract: Background: The COVID-19 pandemic has caused stress on the health care system of many countries worldwide. To accommodate the growing number of critically ill patients requiring mechanical ventilation, hospitals expanded and tried to meet overwhelming demands. Despite this, outcomes of patients after mechanical ventilation were devastating, with high mortality rates. Therefore, this study investigated the survival status and predictors of mortality among mechanically ventilated COVID-19 patients. Methods: A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Furthermore, having delirium as a complication during the follow-up period was reported as a significant predictor of developing cardiac arrest among ICU patients. This finding was conformable with a previous study conducted in the USA, 21 , 34 which that reported excited delirium was a risk factor for sudden cardiac arrest among individuals who required restraints. Even though, we could not find previously reported data regarding association between delirium and cardiac arrest among patients who were admitted to the ICU.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, having delirium as a complication during the follow-up period was reported as a significant predictor of developing cardiac arrest among ICU patients. This finding was conformable with a previous study conducted in the USA, 21 , 34 which that reported excited delirium was a risk factor for sudden cardiac arrest among individuals who required restraints. Even though, we could not find previously reported data regarding association between delirium and cardiac arrest among patients who were admitted to the ICU.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest magnitude of COVID-19 mortality (1.2%) was recorded in the Oromia region ( 41 ), while the highest magnitude (63.3%) was recorded in Addis Ababa ( 53 ). The maximum and minimum incidence rates of COVID-19 mortality were 56.7 per 1,000 persons per day ( 53 ) and 4.7 per 1,000 persons per day ( 46 ), respectively. The majority of studies (61.9%) were conducted between 2020 and 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 98%
“…Three studies ( 46 , 52 , 53 ) were used to examine the relationship between hypertension and COVID-19 mortality. One study ( 46 ) showed a significant association, whereas the other two studies ( 52 , 53 ) revealed no significant association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations